GIS and Housing Principles and Practices - Ramasubramanian, Laxmi (GIS in Action, 2024)
GIS and Housing: Principles and Practices discusses one of the challenges that has not been addressed by Geographic Information Science thus far: how can we use GIS to deal with the complex issues underlying the housing crisis? This book provides GIS technicians and analysts with an overview of US housing challenges and examples of how to effectively integrate spatial thinking to address housing policy questions, while simultaneously introducing housing policy analysts to advanced GIS concepts and techniques to create livable neighborhoods that include housing alternatives beyond the single family. Through numerous examples, the authors advocate for a collaborative approach that encourages professionals, policymakers, and analysts, across different ideological and political perspectives, to confront the multifaceted housing crisis. Features: Examines the historical aspects of housing provision, societal attitudes, demographic shifts, and government policies. Bridges the gaps between housing professionals and GIS experts, facilitating an interdisciplinary approach to address the housing crisis. Explores different challenges that are facing urban, suburban, and rural neighborhoods in different US regions. Provides professionals with the necessary tools for informed decision-making. Proposes solutions that leverage the integrative capacity of GIS to address established housing issues. Advocates for denser housing alternatives to address issues of affordability, supply shortages, and homelessness. This book is intended for graduate students and professionals in housing, community development, urban planning, architecture, and GIS, and anyone curious about learning more about the American housing crisis.